2021
DOI: 10.4236/ojpc.2021.114012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Copper Adsorption by <i>Moringa oleifera</i> Seed Powders

Abstract: In this work, an inexpensive and environmentally friendly natural adsorbent obtained from shelled (GD) and unshelled (GND) Moringa oleifera seeds was used for copper adsorption from aqueous solutions. A series of experiments were performed to assess the parameters influencing the adsorption phenomenon such as pH, adsorbent mass, adsorption equilibrium time and temperature. The kinetic results of adsorption described a pseudo-second order model. The adsorption isotherms are satisfactorily described by the Langm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The physical characterization of carbon paste is noted in numerous works [8,9]. The hulled Moringa seed powder used in this study was characterized by Téhé et al, [20]. The physical characterization carried out by this team with IRTF, DRX, SEM techniques of the shelled seed powder showed a high structural heterogeneity, an amorphous and porous character of the matrix.…”
Section: Influence Of the Quantity Of Moringa Seed Powder On The Redo...mentioning
confidence: 80%
See 2 more Smart Citations
“…The physical characterization of carbon paste is noted in numerous works [8,9]. The hulled Moringa seed powder used in this study was characterized by Téhé et al, [20]. The physical characterization carried out by this team with IRTF, DRX, SEM techniques of the shelled seed powder showed a high structural heterogeneity, an amorphous and porous character of the matrix.…”
Section: Influence Of the Quantity Of Moringa Seed Powder On The Redo...mentioning
confidence: 80%
“…Moringa is also said to be full of numerous minerals, the main ones being sodium (Na), calcium (Ca), magnesium (Mg), etc. [20]. The study of the physicochemical properties of hulled seed powders revealed that these powders constitute a good source of proteins [20].…”
Section: Influence Of the Quantity Of Moringa Seed Powder On The Redo...mentioning
confidence: 99%
See 1 more Smart Citation